Exploring the Components of Green Hospitals Through an Accreditation-Based Approach: A Qualitative Study - Ghasem Abedi; Roya Malekzadeh; Seyedeh Fatemeh Alamdar (Journal of Mazandaran University of Medical Sciences)
Background and purpose: Defining the components of a green hospital has a significant impact on the performance of healthcare systems and the achievement of sustainable health goals. However, the conceptualization of these components remains complex, and there is currently no consensus on the development of appropriate measurement tools. This study aimed to identify and define the components of a green hospital using an accreditation-based approach. Materials and methods: This qualitative study was conducted in 2023. The participants included 17 experts, managers, and policymakers in the healthcare system who were familiar with the concept of green hospitals. Data were collected through semi-structured interviews using purposive sampling, complemented by snowball sampling, and continued until data saturation was reached. The interviews were transcribed, and meaningful units were identified, coded, and categorized based on thematic similarity and conceptual symmetry, then analyzed using a conventional content analysis approach. Results: Analysis of participants’ experiences led to the extraction of six main themes and 18 sub-themes. The identified main themes included management and leadership, hospital building design, green space, energy management, water efficiency, and waste management. The corresponding sub-themes were: environmentally preferable purchasing, strategic planning and policymaking, support from senior management, paper use optimization, appropriate site selection, innovative design, use of sustainable materials, selection of suitable vegetation, allocation of green space, efficient irrigation methods, energy efficiency, use of clean energy, promotion of green transportation, water conservation, wastewater management, non-infectious waste disposal, infectious waste disposal, and chemical waste management. Conclusion: The defined components highlight the multifaceted nature of green hospitals and their essential role in promoting environmentally sustainable development. Strengthening key elements such as management and leadership, hospital building design, green space, energy and water efficiency, and waste management is recommended to more effectively identify, assess, and enhance green hospital performance in accordance with accreditation-based frameworks.